Analisis Daya Dukung Dan Penurunan Kelompok Tiang Bor Pada Menara Transmisi SUTT - Dyah Pratiwi Kusumastuti; Alfinia Milanova (FORUM MEKANIKA, 2023)
In planning the foundation must look at the condition of the subsoil and the situation in the field. drilled piles are mostly chosen if the soil layer in the field is dominated by soft soil and the work area is densely packed with buildings. The 150 kV SUTT transmission tower in Teluk Naga uses drilled piles because the soil layer is dominated by soft soil 12 m thick from the surface and the environment is submerged in water making it impossible to erect. To determine the stability of the foundation there are several factors that need to be reviewed, including bearing capacity and settlement. Bearing capacity analysis on drilled pile foundations can be carried out based on standard penetration test data using the O'neill and Reese method, while settlement calculations can use the Vesic method. The carrying capacity of the group piles obtained in this study was calculated by varying the diameter of 40 cm, 60 cm and 80 cm respectively of 4426.51 kN, 4613.18 kN and 4682.58 kN. While the group piles settlement that occurs is the total of elastic settlement and consolidation settlement of 88.73 mm at 40 cm diameter, 83.37 mm at 60 cm diameter and 85.14 mm at 80 cm diameter.